Socio‑Economic, Health and Ecosystems Vulnerabilities to Climate Change in Rural Areas in Kenya: Implications for Human Capacity Resilience - Kerich, Emmy C.; Aaron, Naomy Chepchumba; Kendagor, Ruth Jeruiyot; Tarus, Susan; Awino, Molly; Kanake, Mercy Kananu; Okademi, Nancy; Sergon, Philomena C.; Kinyua, Joyce Njeri (Prevention and Treatment of Natural Disasters, 2025)
The recent decades have brought multiple studies of natural and social systems confirming climate change and its impact on the environment and human populations. Rural Kenya, home to 70% of the population and the backbone of its agrarian economy, is particularly susceptible due to its reliance on climate‑sensitive sectors. The study emerges from growing concerns about how recurring climate shocks perpetuate cycles of poverty, food insecurity and diminished adaptive capacity in rural communities, threatening Kenya’s sustainable development goals. Further, existing studies often address socio‑economic, health and ecosystem vulnerabilities in isolation, obscuring critical interdependencies. This scoping review aims to systematically map the interconnected vulnerabilities in rural Kenya and synthesize their implications for human capacity resilience. This scoping review, guided by the theory of climate vulnerability (exposure, sensitivity, adaptive capacity), systematically mapped these interconnected vulnerabilities in rural Kenya. Following a pre‑registered protocol and PRISMA‑ScR guidelines, 110 articles from 2010 onwards were analyzed using descriptive and thematic analysis. Findings reveal widespread socio‑economic vulnerability, especially in ASALs, driven by droughts, erratic rainfall and rising temperatures, compounded by poverty and gender inequality. Climate change also elevates health risks, increasing infectious diseases, malnutrition, and mental health burdens. Critical ecosystems are degrading, further destabilizing livelihoods. Vulnerable populations, including women, children, pastoralists and PWDs), bear the brunt of these impacts due to structural inequities. All these challenges severely erode human capacity resilience, overwhelming traditional coping strategies. Recommendations prioritize ecosystem‑based adaptation, livelihood diversification, and inclusive governance to build sustainable climate resilience in rural Kenya.